Does Cannabis Intake Protect Against Non-alcoholic Fatty Liver Disease? A Two-Sample Mendelian Randomization Study - Wang, Xiaokun; Liu, Zhipeng; Liu, Wanqing (Frontiers in Genetics, 2020)
Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. Previous observational studies suggested that cannabis use may be associated with a lower risk for NAFLD but the causal relationship remains unclear. We aim in this study to examine the causal effect of cannabis consumption on the risk of NAFLD using a Mendelian randomization analysis. Clarifying this causal effect is important for cannabis-based drug discovery for NAFLD. Methods: We used data from the largest-to-date GWAS meta-analysis on lifetime use of cannabis (yes or no) consisting of three cohorts (International Cannabis Consortium (ICC), 23andMe, and the UK Biobank) of European ancestry (total N=184,765). We also used other GWAS data on cannabis use dependence and cannabis use disorder. The NAFLD GWAS data were generated from the UK Biobank population (1,122 cases and 399,900 controls). The inverse variance weighted (IVW) method was used to assess the causal impact of cannabis lifetime use on the risk of NAFLD. We also performed a sensitivity analysis using weighted median estimator and MR-Egger. Results: There was no statistically significant causal effect between either the lifetime cannabis use, cannabis use dependence or cannabis use disorder and the risk for NAFLD (p>0.05 for all tests). No significant pleotropic effect was observed based on both MR-PRESSO global test (p = 0.99) and the modified Q’ statistics. However, the study may be underpowered. Conclusion: Our results demonstrated no evidence that cannabis consumption has a causal effect of protection against the development of NAFLD.